Image analysis of the seeds and seedlings of Vigna radiata L. - Fernandes Abud, Haynna (Revista Ciência Agronômica, 2021)
In a griculture it is essential to use high-quality seeds capable of expressing their maximum vigour. Image analysishas been used to assess the quality of seed batches. The aim of this study was to characterise seedling growth in the mung beanand the external morphology of the seeds using image analysis, and identify the morphological characteristics associated with highphysiological potential. The trial was conducted using two accessions of the mung bean (yellow and green). The 1000-seed weight andgermination test were carried out in an initial characterisation. Using image analysis, the following parameters were evaluated in theseeds: area, perimeter, colour, circularity, length and width. In the seedlings, the length and dry matter of the shoots and root systemwere evaluated together with the total dry matter. A germination of 100% and 89.5%, and 1000-seed weight of 54.91 g and 35.49 gwere found for the yellow and green mung beans. In the yellow mung bean, the largest seeds showed a direct relationship with the othermorphological parameters of the seeds in addition to a strong relationship between the length of the shoots and the root system. In thegreen mung bean, there was a direct relationship between seed area and perimeter, length, width and colour; however, the best seedlingperformance was found in the smaller seeds. The use of image analysis makes it possible to identify seeds of greater physiologicalpotential, which allows more-vigorous batches of mung bean seeds to be selected.